2019
DOI: 10.15252/embr.201847425
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocation of cyclin C stimulates intrinsic apoptosis through Bax recruitment

Abstract: Intrinsic apoptosis requires mitochondrial outer membrane disruption triggered by recruitment, activation, and oligomerization of the Bcl‐2 homology protein Bax. Following oxidative stress, we demonstrated that the transcriptional regulator cyclin C is released into the cytosol where it directs mitochondrial fragmentation and efficient apoptotic induction. This study reveals that cytoplasmic cyclin C is required for both normal Bax activation and its efficient mitochondrial localization. This activity appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…Recently, it has been shown that Cyclin C associates with Bcl-2 homology containing protein BAX and tethers it with the stress-induced mitochondrial fission complex in the mammalian cell line. This provides sufficient dwell time on mitochondria for BAX to be recognized by the BH3 containing proteins leading to initiation of PCD in the mammalian cell line [88]. Since Cyclin C translocation from the nucleus to the cytoplasm is a conserved process from the yeast to humans, this finding of TDP-43-induced Cyclin C translocation in yeast may have direct relevance to the ALS pathology [83,85,88,91,92].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Recently, it has been shown that Cyclin C associates with Bcl-2 homology containing protein BAX and tethers it with the stress-induced mitochondrial fission complex in the mammalian cell line. This provides sufficient dwell time on mitochondria for BAX to be recognized by the BH3 containing proteins leading to initiation of PCD in the mammalian cell line [88]. Since Cyclin C translocation from the nucleus to the cytoplasm is a conserved process from the yeast to humans, this finding of TDP-43-induced Cyclin C translocation in yeast may have direct relevance to the ALS pathology [83,85,88,91,92].…”
Section: Discussionmentioning
confidence: 90%
“…Alike to the cnc1 yeast presence of functional mitochondria was also essential for the rescue in the dnm1 yeast. It is noteworthy that an inhibitor of Drp1 and Fis1 interaction was previously found to relieve the TDP-43-induced mitochondrial fragmentation and cytotoxicity [88]. Surprisingly however, the toxicity of TDP-43 was not rescued in the fis1yeast the reason for which is not completely understood.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The binding domain on cyclin C directing this interaction is termed the holoenzyme-associating domain or HAD (Cooper and Strich, 1999). We recently demonstrated that addition of a cellpenetrating stapled HAD mimetic peptide (S-HAD) induced cyclin C nuclear release in the absence of stress (Jezek et al, 2019). The finding that cyclin C is present in thyroid cancer cell lines prompted the question of whether S-HAD had a similar activity in PDTC cell line D316.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its role in transcription, cyclin C also has a Cdk8independent role in mediating stress-induced mitochondrial fragmentation and mitochondrial outer membrane permeability (MOMP) (Ganesan et al, 2019;Wang et al, 2015), the commitment step to intrinsic mitochondrial-dependent regulated cell death type 1 (RCD-1) (Galluzzi et al, 2015). This function is highly conserved, as cyclin C is required for mitochondrial fission and stress-induced cell death in budding yeast (Cooper et al, 2014) and mammalian cells (Jezek et al, 2019). Finally, deleting cyclin C protects mouse embryonic fibroblast (MEF) cells from RCD-1 induced by oxidative stress or the anti-cancer drug cisplatin (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%